Systemic Hypertension in Companion Animals: A Review - Sangwan, Tanvika; Saini, Neetu (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
With the rapid pace of westernization, economic development and increasing pets as a member of nuclear families, human and companion animals do share a common sedentary behaviour and unhealthy feeding habits. These insalubrious habits predispose them to the lifestyle diseases also known as non-communicable chronic diseases which are increasing at an alarming rate in humans as well as in companion animals (Pappachan, 2011; Chandler et al., 2017). These diseases include hypertension, obesity, diabetes mellitus and dyslipidemia, which are considered to be the major risk factors for cardiovascular diseases like myocardial ischemia and stroke in human beings (Pappachan, 2011). But, in contrast to humans, myocardial ischemia and stroke due to hypertension is very rare in dogs and cats (Elliott, 2020). Systemic hypertension also known as the silent killer in human medicine is a newly recognized disease in veterinary that affects the essence and survivability of companion animals (Dixon-Jimenez et al., 2011; Elliott and Brown, 2020).
Keywords: Systemic; Hypertension; Companion